Validasi Item Tedeschi-Calhout Post Traumatic Growth Inventory Scale Pada Istri Korban Perselingkuhan - Adetya, Sandra; Corsini, Andreas; Septiyani, Diah Ayu (Lembaga Penelitian, Pengabdian Kepada Masyarakat dan Publikasi (LPPMP), 2023)
This study aims to validate the posttraumatic growth scale developed by Tedeschi and Calhout, known as the 21-item Tedeschi-Calhout (21-item PTG) for wife respondents who have had an affair. The scale validation method uses the Single Trial Administration approach which produces an estimate of internal consistency reliability using the Chronbach's Alpha method. The 21-item Tedeschi-Calhout (21-item PTG) validation sample used in this study consisted of 260 wives who were victims of infidelity. working. From the results of statistical analysis using SPSS software, it was found that all items on the 10-item CD-RISC scale were declared feasible. The reliability coefficient value was 0.829, so it can be concluded that the 21-item PTG scale is reliable and can be used for data collection.